Analisis Kesalahan Ejaan Dalam Surat Dinas Di Kantor Kecamatan Ngrampal Kabupaten Sragen - Sudarsih, Nining, Drs. Yakub Nasucha, M.Hum (2016)
There are three objectives in this study. (1) knowing errors lettering, (2) know the writing errors of punctuation, and (3) to know the word errors. This research is descriptive qualitative research. The subject of this research is to analysis of spelling errors in the letter at the Ngrampal District Office. Data collection techniques in this study using observation, document, see and record. Mechanical testing the validity of the data using triangulation theory. Data were analyzed using a unified method consisting of a unified method intralingual and ekstralingual. The results of this study found an error writing letters as much as 35 data, the writing of the letter which includes the writing of a capital letter, writing italics, writing bold, writing errors of punctuation as many as 27 data, the writing errors of punctuation includes writing a semicolon, a comma, a sign dots, dashes and the word errors by 16 data word errors consisted of writing stands and combinations of words. Thus, the overall number of spelling mistakes as much as 84 data. Keywords: analysis of errors in spelling, capitalization, spelling, writing, punctuation, and official letter.